Risk practices among the young people: Preliminary study on ordeals conducts (Psicologia USP, 2016)
This paper reports the discussion of an ongoing study on the meaning of risk practices by young people in the transition to adulthood and preliminary results of a pilot study using a questionnaire about trial by ordeal function. Based on the return to the concept of trial by ordeal conducts, we seek to deepen the analysis of risk practices involving young Brazilians as symptoms of a malaise that they experience in the transition to adulthood. We conducted a pilot experiment with the application of a questionnaire that evaluates the trial by ordeal function. The initial sample included 82 university students of both sexes. The preliminary results were promising in the comparison of the four factors by sex of subjects and in correlation with age. To advance this research perspective, contributions should be made to the thorough understanding of these practices as well as to the development of preventive and protective actions for young people.